Use of Composite End Points in Early and Intermediate Age-Related Macular Degeneration Clinical Trials: State-of-the-Art and Future Directions - Terheyden, Jan Henrik; Schmitz-Valckenberg, Steffen; Crabb, David P.; Dunbar, Hannah; Luhmann, Ulrich F.O.; Behning, Charlotte; Schmid, Matthias; Silva, Rufino; Cunha-Vaz, José; Tufail, Adnan; Weissgerber, Georges; Leal, Sergio; et al. (Ophthalmologica (Basel), 2021)
The slow progression of early age-related macular degeneration (AMD) stages to advanced AMD requires the use of surrogate end points in clinical trials. The use of combined end points may allow for shorter and smaller trials due to increased precision. We performed a literature search for the use of composite end points as primary outcome measures in clinical studies of early AMD stages. PubMed was searched for composite end points used in early/intermediate AMD studies published during the last 10 years. A total of 673 articles of interest were identified. After reviewing abstracts and applicable full-text articles, 33 articles were eligible and thus included in the qualitative synthesis. The main composite end point categories were: combined structural and functional end points, combined structural end points, combined functional end points and combined multicategorical end points. The majority of the studies included binary composite end points. There was a lack of sensitivity analyses of different end points against accepted outcomes (i.e., progression) in the literature. Various composite outcome measures have been used but there is a lack of standardization. To date no agreement on the optimal approach to implement combined end points in clinical studies of early stages of AMD exists, and no surrogate end points have been accepted for AMD progression.